Origins of residual stress in thin films: Interaction between microstructure and growth kinetics. (15th November 2016) - Engwall, A.M.; Rao, Z.; Chason, E.
Abstract: Thin films can develop large residual stresses during their growth that significantly impact their performance. Therefore, there is a need to understand how the stress is related to the developing film structure and underlying kinetic processes. In this work, we describe measurements of stress and the corresponding grain structure during electrodeposition of Ni and Cu films. For Ni deposition, the grain size stays nearly constant during growth and the stress reaches a nearly constant steady-state. For Cu deposition, the grain size grows as the thickness increases and the microstructural evolution affects the evolution of the stress. To remove the effect of subsurface grain growth on the stress, measurements were also done with periodic pauses that allowed the stress induced by grain growth to saturate. We interpret the results in terms of a kinetic model for stress evolution that focuses on the developing boundary between adjacent grains while the film is deposited. The effect of grain growth on stress for different types of microstructural evolution is also discussed. After accounting for the stress from subsurface grain growth, the results are consistent with the model for the dependence on growth rate and grain size at the surface. Graphical abstract: Highlights: Microstructural evolution during thin film growth affects the corresponding evolution of stress. Stress is modified by the changing grain size at the surface and grain growth below the surface. Measurements with pauses allow grain growth to saturate and eliminate its effect on the stress. A kinetic model explains the dependence of the stress on the growth rate and grain size at the surface.